The racial and ethnic typification of crime, and the criminal typification of race and ethnicity in local television news - Chiricos, Theodore G. (Journal of research in crime and delinquency, 2002)
Local news programming from three television stations in Orlando, Florida was analyzed for racial and ethnic content in relation to crime. The data show that Blacks are not overrepresented among TV news suspects relative to their proportion in the population or among those arrested in Orlando. Hispanics are slightly overrepresented in relation to their numbers in the population. Qualitatively, Blacks and especially Hispanics who appear as crime suspects do so in more threatening contexts than Whites. Blacks are more likely to appear as criminal suspects than as victims or positive role models, but this pattern is especially amplified for Hispanics. These results suggest that local TV news may contribute to the social construction of threat in relation to Blacks and Hispanics, a condition that is associated with fear of crime, "modern racism," and the mobilization of various social controls and exclusions